Caring for refugees: Training the health workforce towards structural competence and responsibility. (30th September 2020) - Ziegler, S; Kratochwill, S; Jahn, R; Bozorgmehr, K; Rast, E
Abstract: Background: Providing high-quality health care to superdiverse populations of newly arrived refugees poses specific structural, organisational, communicative, ethical and medical challenges that medical students in Europe are often not systematically prepared for. We created a clinical elective, to enable future doctors to identify and address the needs of refugee-patients and deliver high quality care to this population. Objectives: We provided medical, structural, administrative, communicative and socio-cultural knowledge and skills training through seminars (24 h) and field placements (2 days) in a reception centre clinic for refugees. The training aimed at stimulating a systematic professional, personal, scientific, and political reflection, to foster social accountability, and raise awareness for the special situation of vulnerable groups. The didactic concept built on multidisciplinary lectures, student centred teaching, and research-oriented learning. Mainly qualitative summative and formative evaluations were applied to improve the course and examine training outcomes. Results: A total of 112 students completed the elective over four terms, 50 evaluated it, of which 80% considered it worthwhile. Self-reported competencies in caring for refugee patients were low at the beginning and increased after course completion. The most important learning outcomes were knowledge of the asylum-law, gaining a multi-perspective view through multiple disciplinary lenses as well as professional, ethical, interpersonal and political insights during practical experience and reflection. Conclusions: A multidisciplinary course that combines theory, practice and reflection, can prepare students for the complex challenges medical professionals face in caring for refugees. This could help strengthen their professional role as advocates of health equity. Our innovative didactical approach, course and evaluation concept can inspire the creation and implementation of similar courses elsewhere. Key messages: The health workforce needs training to identify, address and help compensate respective barriers to health care and foster equal opportunities to health for refugees. A multidisciplinary teaching concept, tailored to specific target groups can help make future doctors and nurses in Europe fit for their responsibility and work in plural and ever changing societies.